Risk Factors For Rate of Decline in Forced Expiratory Volume in One Second in Children and Adolescents with Cystic Fibrosis - Konstan, Michael W.; Morgan, Wayne J.; Butler, Steven M.; Pasta, David J.; Craib, Marcia L.; Silva, Stefanie J.; Stokes, Dennis C.; Wohl, Mary Ellen B.; Wagener, Jeffrey S.; Regelmann, Warren E.; Johnson, Charles A. (The Journal of pediatrics, 2007)
To characterize the rate of decline of forced expiratory volume in 1 second (FEV 1) in children and adolescents with cystic fibrosis and to identify and compare risk factors associated with FEV 1 decline. The rate of decline in FEV 1% predicted over 3 to 6 years in 3 different age groups was determined. Risk factors for decline were identified and compared among and within age groups as a function of disease severity with repeated-measures, mixed-model regression. Mean (±SD) baseline FEV 1% predicted was 88.4% ± 20.5% for 6- to 8-year-olds (n = 1811), 85.3% ± 20.8% for 9- to 12-year-olds (n = 1696), and 78.4% ± 22.0% for 13- to 17-year-olds (n = 1359). Decline in FEV 1% predicted/year was −1.12, −2.39, and −2.34, respectively. High baseline FEV 1 and persistent crackles were significant independent risk factors for decline across all age groups. Female sex, Pseudomonas aeruginosa infection, low weight-for-age, sputum, wheezing, sinusitis, pulmonary exacerbations treated with intravenous antibiotics, elevated liver test results, and pancreatic insufficiency were also identified as independent risk factors in some age groups. This study identifies risk factors for FEV 1 decline in children and adolescents with cystic fibrosis. Clinicians should not be reassured by high lung function, particularly in young children, because this factor, among others, is independently associated with steeper decline in FEV 1.